2017
DOI: 10.1111/ipd.12316
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' attitudes towards acute pharmacological pain management in children and adolescents

Abstract: SPDs recommend preoperative analgesics more often than GDPs do. GDPs seem to underuse local anaesthetics when treating children and adolescents. SPDs also use pain management strategies more frequently than GDPs. Among GDPs, pain management is less frequent when treating primary teeth than permanent teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 12 publications
(21 reference statements)
2
25
0
1
Order By: Relevance
“…The results from Paper I regarding never or rarely using LA among younger children are concordant to the conclusion by Berlin et al, who raised questions about dentists' use of pain-reducing strategies and an underuse of LA when treating children and adolescents (49).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The results from Paper I regarding never or rarely using LA among younger children are concordant to the conclusion by Berlin et al, who raised questions about dentists' use of pain-reducing strategies and an underuse of LA when treating children and adolescents (49).…”
Section: Resultssupporting
confidence: 83%
“…This result is supported by a Swedish study that concluded that there is an underuse of LA when performing dental treatment among children and adolescents. Further, they report that PDs used LA equally often when treating primary and permanent teeth compared to GDPs, who used less LA when treating primary teeth (49).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, and the fact that all administration of pharmacologic agents comes with a risk (Matok et al 2016;Norman et al 2014), it can be questioned if there is any reason for clinical guidelines in this area. Analogously, there is no rationale for introducing or routinely using administration of analgesics in conjunction with routine dental treatments such as filling therapies or uncomplicated extractions (Berlin et al 2018). When considering use of pharmacological agents with children, there must be a clear-cut reason for doing so.…”
Section: Discussionmentioning
confidence: 99%
“…No systematic review on postoperative administration of analgesics for preventing/reducing postoperative pain has been identified. Despite the lack of scientific support, there are reports of dentists using oral analgesics to reduce pain in conjunction with extractions and filling therapy (Berlin et al 2018). Thus, there is a need for well-designed clinical studies to evaluate the effect of oral analgesics to prevent pain, and based on this to formulate clinical guidelines.…”
Section: Introductionmentioning
confidence: 99%